O-GlcNAc Modification During Pregnancy: Focus on Placental Environment - Lima, Victor Vitorino; Dela Justina, Vanessa; dos Passos, Rinaldo Rodrigues; Volpato, Gustavo Tadeu; Souto, Paula Cristina S.; San Martin, Sebastian; Giachini, Fernanda Regina (Frontiers in Physiology, 2018)
Successful placentation is a key event for fetal development, which commences following embryo implantation into the uterine wall, eliciting decidualization, placentation, and remodeling of blood vessels to provide physiological exchange between embryo-fetus and mother. Several signaling pathways are recruited to modulate such important processes and specific proteins that regulate placental function are a target for the glycosylation with O-linked β-N-acetylglucosamine (O-GlcNAc), or O-GlcNAcylation. This is a reversible post-translational modification on nuclear and cytoplasmic proteins, mainly controlled by O-GlcNAc transferase (OGT) and O-GlcNAcase (OGA). O-GlcNAcylation has been implicated as a modulator of proteins, both in physiological and pathological conditions and, more recently, O-GlcNAc has also been shown to be an important modulator in placental tissue. In this mini-review, the interplay between O-GlcNAcylation of proteins and placental function will be addressed, discussing the possible implications of this post-translational modification through placental development and pregnancy.